2013
DOI: 10.1074/jbc.m113.491688
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Division Proteins FtsZ and ZipA Induce Vesicle Shrinkage and Cell Membrane Invagination

Abstract: Background: Before constriction ZipA anchors FtsZ to the E. coli inner membrane as part of the cell division proto-ring. Results: Dynamic FtsZ polymers shrink ZipA-containing vesicles whereas excess of ZipA invaginates the E. coli membrane destroying the permeability barrier. Conclusion: Constriction forces can be evidenced both in bacteria and in vesicles. Significance: Defined bacterial elements reproduce division functions when assembled in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 52 publications
3
78
1
2
Order By: Relevance
“…Procedures to incorporate FtsZ inside giant vesicles, formed by reverse emulsion, with ZipA artificially incorporated at the inner membrane face have recently been optimized (Cabré et al, 2013). These vesicles have been made permeable allowing the control of FtsZ polymerization inside them by externally added ligands that promote assembly, such as GTP and Mg…”
Section: Note Added In Proofmentioning
confidence: 99%
“…Procedures to incorporate FtsZ inside giant vesicles, formed by reverse emulsion, with ZipA artificially incorporated at the inner membrane face have recently been optimized (Cabré et al, 2013). These vesicles have been made permeable allowing the control of FtsZ polymerization inside them by externally added ligands that promote assembly, such as GTP and Mg…”
Section: Note Added In Proofmentioning
confidence: 99%
“…Simplified lipid-cytoskeletal protein complexes system have been reconstituted in model membrane systems as GUVS, liposomes and supported lipid membranes (Merkle et al, 2008;Cabré et al, 2013;Osawa and Erickson, 2013;Pontani et al, 2009;MateosGil et al, 2012a) using different ways to anchor the proteins to the membranes. Modeling the segregation of lipid phases under the presence of cytoskeletal proteins is challenging because it is important to include the self-assembling properties of the proteins.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above in the context of early cell division, a possible minimal divisome architecture inspired from bacterial cytokinesis would consist of FtsZ protofilaments anchored to the liposome membrane by native auxiliary proteins such as the actin homologue FtsA or ZipA (Osawa et al 2008(Osawa et al , 2009Osawa and Erickson 2013;Jimenez et al 2011;Cabre et al 2013). In the absence of a cell wall mimicry, FtsZ assisted by FtsA was suggested as the simplest machinery to recapitulate all essential steps of cellular division in lipid vesicles: Z ring formation, force generation to distort the liposome membrane, progressive constriction of the Z ring and completed division (Osawa and Erickson 2013).…”
Section: Expression Of Membrane Proteins Directly Involved In Cell DImentioning
confidence: 99%
“…Studies using the conventional reconstitution approach based on purified proteins have revealed important insights on the mechanisms of liposome deformation evoked, for instance, by MinE (Shih et al 2011), amphiphysin 1 (Sorre et al 2012), I-BAR domain proteins (Saarikangas et al 2009), clathrin (Dannhauser and Ungewickell 2012), and FtsZ with its associated membrane-binding proteins (Osawa et al 2008;Cabre et al 2013). However, it has not been reported yet that in situ expressed proteins, i.e.…”
Section: Experimental Evidence Of Genetically Controlled Deformation mentioning
confidence: 99%